If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w + -6)(w + 2) = 0 Reorder the terms: (-6 + w)(w + 2) = 0 Reorder the terms: (-6 + w)(2 + w) = 0 Multiply (-6 + w) * (2 + w) (-6(2 + w) + w(2 + w)) = 0 ((2 * -6 + w * -6) + w(2 + w)) = 0 ((-12 + -6w) + w(2 + w)) = 0 (-12 + -6w + (2 * w + w * w)) = 0 (-12 + -6w + (2w + w2)) = 0 Combine like terms: -6w + 2w = -4w (-12 + -4w + w2) = 0 Solving -12 + -4w + w2 = 0 Solving for variable 'w'. Factor a trinomial. (-2 + -1w)(6 + -1w) = 0Subproblem 1
Set the factor '(-2 + -1w)' equal to zero and attempt to solve: Simplifying -2 + -1w = 0 Solving -2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1w = 0 + 2 -1w = 0 + 2 Combine like terms: 0 + 2 = 2 -1w = 2 Divide each side by '-1'. w = -2 Simplifying w = -2Subproblem 2
Set the factor '(6 + -1w)' equal to zero and attempt to solve: Simplifying 6 + -1w = 0 Solving 6 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1w = 0 + -6 -1w = 0 + -6 Combine like terms: 0 + -6 = -6 -1w = -6 Divide each side by '-1'. w = 6 Simplifying w = 6Solution
w = {-2, 6}
| 2.89=x% | | 7x=6x+6 | | x+5y=33 | | 3x^2+3y^2=48 | | 6*-2/3+8 | | 4+2x=5x+16 | | x+3=25/5 | | n^2-19n+88= | | 3/3x2-5x-2 | | 9-9/10 | | 15y-9=36 | | 3y^2-5=16 | | 19.36+22.93= | | 3x^2=17-20 | | 10000=19.36+22.93 | | 10p-9-2p+12= | | 21-(5-21)*5/8 | | 12-24*(-5/8) | | -7x-7=63 | | 5a+10b=30 | | 0.5p^2=4p-8 | | -2a^2+6a=5 | | 9m-16=m | | 5*8+9+4=53 | | 0.5/2.5 | | 145000000/1.16= | | -x^2-15x+4=0 | | 5*(8+9)+4=89 | | 2x-25=55 | | 504*.14= | | 5b+2p=144 | | (15n^2-5n+45)/5 |